Screen-based digital learning methods in radiation oncology and medical education. (December 2022) - Kok, David L.; Dushyanthen, Sathana; Peters, Gabrielle; Sapkaroski, Daniel; Barrett, Michelle; Sim, Jenny; Eriksen, Jesper Grau
Abstract: The field of radiation oncology is rapidly advancing through technological and biomedical innovation backed by robust research evidence. In addition, cancer professionals are notoriously time-poor, meaning there is a need for high quality, accessible and tailored oncological education programs. Digital learning (DL) is well-placed to cater to these needs, as it provides teaching options that can be delivered flexibly and on-demand from anywhere in the world. The evidence for usage of these techniques in medical education has expanded rapidly in recent years. However, there remains many reservations in the oncological community to adopting and developing DL, largely due to a poor familiarity with the pedagogical evidence base. This article will review the application of the screen-based DL tools that are at educators' disposal. It will summarize best-practice in developing tailored, made-for-screen videos, gamification, and infographics. It also reviews data behind the following practical tips of 1) strategically combining text with graphics to decrease cognitive load, 2) engaging users through use of interactive elements in digital content, and 3) maximizing impact through thoughtful organization of animations/images. Overall, the digital space evolving is well placed to cater to the evolving educational needs of oncology learners. This review and its practical tips aim to inspire further development in this arena, production of high-yield educational products, use of engaging delivery methods and programs that are tailored to individual learning needs.